Pengetahuan Ibu Menyusui tentang Pemberian ASI Eksklusif di Klinik Bertha Tahun 2022 - Hetty Gustina Simamora; Elsa Frida Tarigan; Nagoklan Simbolon (STIKes Santa Elisabeth Medan, 2023)
Introduction : The best nutrition at the beginning of a baby's life is breast milk. Exclusive breastfeeding is recommended for the first six months of a baby's life without any other additional food ingredients.Method : This study uses a descriptive design, namely survey research that tries to explore how and why health phenomena occur. This research aims to find out the knowledge of breastfeeding mothers about exclusive breastfeeding at the Bertha Clinic in 2022Result : The research results obtained from the knowledge of breastfeeding mothers about exclusive breastfeeding at the Bertha Clinic, the majority of mothers work as housewives with a percentage of 96.2% and the knowledge of breastfeeding mothers about exclusive breastfeeding has good knowledge with a percentage of 100%.Conclusion : The knowledge of breastfeeding mothers about exclusive breastfeeding at the Bertha clinic is good and it is hoped that mothers will continue to apply their knowledge in caring for their babies.